Temperature-Sensitive Paint Applications in the Heat Transfer Analysis of 90° Elbow Microchannel Flow with Sharp and Curved Turns. (August 2020) - Huang, Chih-Yung; Lin, Jhih-Ren; Liou, Tong-Miin
ABSTRACT: This study presents the heat transfer analysis of 90° elbow microchannel flow with sharp and curved turn designs. Experimental technique of temperature-sensitive paint was adapted in the experiment for measuring both fluid and surface temperature. The detailed information of fluid and surface temperature data were successfully acquired with a microscope system at Reynolds number varying from 50.5 to 101.1. Micro heaters were fabricated and positioned underneath the microchannel to provide the constant heat flux boundary condition. The utilization of micro heaters can prevent the axial heat conduction. The Nusselt number contours were obtained in this study with sharp and curved corners, which can provide detailed information of localized region with high and low heat transfer. The experimental approach performed in this study could be applied in the future for micro heat exchanger or heat sink design with complex microchannel systems.